Androgen receptor dampens tissue factor expression via nuclear factor‐κB and early growth response protein 1. (13th March 2018) - Hoesel, B.; Mussbacher, M.; Dikorman, B.; Salzmann, M.; Assinger, A.; Hell, L.; Thaler, J.; Basílio, J.; Moser, B.; Resch, U.; Paar, H.; Mackman, N.; et al.
Abstract : Essentials Androgen deprivation increases the rate of venous thromboembolism in prostate cancer patients. We characterized androgen receptor‐mediated tissue factor regulation in prostate epithelial cells. Androgen receptor is dampening tissue factor expression in prostate epithelial cells. Androgen deprivation could enhance tissue factor expression and raise venous thromboembolism rates. Summary: Background: Prostate cancer is one of the leading causes of cancer death in men. Advanced prostate cancer is usually treated by androgen deprivation therapy (ADT), which is aimed at reducing circulating testosterone levels to reduce cancer growth. There is growing evidence that ADT can increase the rate of venous thromboembolism (VTE) in prostate cancer patients. The tissue factor (TF) gene is one of the most important mediators of coagulation and VTE, but, so far, there are limited data on androgen receptor (AR)‐mediated TF gene expression. Objectives: To characterize AR‐mediated TF regulation in vitro and in vivo . Methods: We used the androgen‐dependent prostate cancer cell lines LNCaP and MyC‐CaP to test whether TF expression is regulated by AR. Furthermore, we cloned the TF gene promoter into a luciferase reporter vector to identify the transcription factor‐binding sites that mediate TF regulation downstream of AR. Finally, we used castration experiments in mice to characterize AR‐mediated TF regulation in vivo . Results: TF is directly regulated by AR. In LNCaP cells, nuclear factor‐κB signaling and EGR1 mediate TF expression. By using castration experiments in mice, we could detect upregulation of TF and early growth response protein 1 mRNA and protein expression in prostate epithelial cells. Conclusion: AR is crucial for dampening TF expression, which could be important for increased TF expression and TF‐positive microvesicle release in androgen‐deprived prostate cancer patients.